Class consciousness in the 2012 labour disputes at Marikana, North West Province, South Africa - Molepo, Matshipi Moses (University of Limpopo, 2017)
The purpose of this study was to explain the events surrounding the Marikana miners’ strike in 2012, using Marxism’s concept of class consciousness. The labour disputes witnessed at Marikana in 2012 represent one of the major labour movements that South Africa has witnessed since the inception of democracy. This study adopted qualitative research methods to inquire into the events of the Marikana 2012 labour disputes. Methods used in this study include qualitative research, descriptive research design, Marxism critical inquiry, purposive sampling and critical discourse analysis. Moreover, the study investigated employee relations in the mining sector. In addition, this study also examined the Marikana miner’s working and living conditions and probed the role of social control agencies, including, trade unions, bargaining councils and the police, during the protests. This study proposes a fair distribution of wealth in the mining sector and the removal of the Migrant Labour System. Additionally, this study recommends transparency in the mining sector, the transformation of the education system and the restructuring of trade unions.
Thesis (M. A. (Sociology)) --University of Limpopo, 2017
Keywords: Labour disputes; Collective behaviour; Protests; Natural resources; Class consciousness; Proletariat; Bourgeoisie and Marikana; Class consciousness.; Labour disputes -- Japan; Strikes and lockouts -- Law and legislation